An Investigation of Habitual Characteristics of Cognitive Reactivity and Depressive Rumination in a University Sample - Sólveig Anna Daníelsdóttir 1992- (2018)
Objective: Depressive rumination and cognitive reactivity (CR) are established psychological vulnerability factors for recurrent depression. It has recently been proposed that rumination might be a form of mental habit. Furthermore, based on how CR is defined also gives reason to examine CR as a mental habit. The aim of the present study was to explore if rumination and CR are associated with habitual characteristics of negative thought. In addition, the aim was to determine if the relationship of CR and rumination with habitual characteristics of negative thoughts is mediated by habitual responding in everyday life. Method: Participants were 115 students enrolled at the University of Iceland. They were assessed on self-report measures of rumination, CR, habitual characteristics and habitual responding among other constructs. Participants also completed experimental tasks on rumination and CR. Results: As predicted, a strong relationship was found between habitual characteristics and rumination tendencies as well as with CR, measured with self-report. However, contrary to predictions, these results were not replicated using established experimental tasks. Additional analyses showed that the relationship between rumination and CR with habitual characteristics is indeed partly mediated by habitual responding. Conclusion: The findings of the present study suggest that habit plays an important role in both depressive rumination and CR. In addition, the findings indicate that those who have a higher tendency for habitual responding are also more likely to show a stronger relationship between habitual characteristics of negative thought with both rumination and CR. It is therefore possible that those who rely more on habitual responding in everyday life are more likely to develop habitual vulnerability factors.